1962
DOI: 10.1017/s0003356100040733
|View full text |Cite
|
Sign up to set email alerts
|

Milk production in East African zebu cattle

Abstract: An analysis has been made of milk production data from indigenous East African zebu cattle at the Baraton, Maseno and Sangalo Livestock Improvement Centres in Kenya, covering a period of twenty-five to thirty years.The relationships between milk production and length of lactation, dry period, calving interval, month of calving and age were examined. Lactation length accounted for from 53% to 66% of the total variance in milk yield. Variations in length of dry period caused significant differences in milk yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

1962
1962
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 4 publications
3
5
0
Order By: Relevance
“…The variability in the production traits and lactation length was very high as evident from the coefficients of variation for their traits, which was more than 50% for first two production traits and more than 40% for the last two traits. The higher variability observed in this study for 305-day and total lactation yields was in agreement with the reports of ALIM (1960, '62), GALUKANDE et al (1962), ACHARYA and LUSH (1968), BALAINE et al (1970), MOULICK et al (1972 and JOHAR and TAYLOR (1973) in different breeds of tropical dairy cattle. The coefficient of variation in their reports ranged from 40 to 75% for first lactation milk yield.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The variability in the production traits and lactation length was very high as evident from the coefficients of variation for their traits, which was more than 50% for first two production traits and more than 40% for the last two traits. The higher variability observed in this study for 305-day and total lactation yields was in agreement with the reports of ALIM (1960, '62), GALUKANDE et al (1962), ACHARYA and LUSH (1968), BALAINE et al (1970), MOULICK et al (1972 and JOHAR and TAYLOR (1973) in different breeds of tropical dairy cattle. The coefficient of variation in their reports ranged from 40 to 75% for first lactation milk yield.…”
Section: Resultssupporting
confidence: 93%
“…This results in a large variability in the production traits besides the disconnectedness of sires with years and herds. The coefficient of variation for first lactation milk yield in tropical dairy cows is quite high (more than 35 percent) as compared to less than 20 percent in temperate dairy cattle (ALIM, 1960; GALUKANDE et al, 1962;MAHADEVAN 1966 RAO and SUNDARESAN 1979). The genetic parameters for different traits are generally estimated after adjusting the records for environmental factors using the constants obtained in the first run with a model including only environmental effects and then using a model with only sires in the second run.…”
Section: Introductionmentioning
confidence: 99%
“…This compares with the figures given by Galukande et al (1962) for indigenous Zebu stock -823 kg in 239 days (with 123 days dry period). As it turned out its efforts proved highly successful and KCC still exists although it appears that there is now a move to have it broken down into localized fragments.…”
Section: Background Of the Kenya Dairy Industrysupporting
confidence: 76%
“…Semenye (1987) observed that the lactation curve of the Maasai Zebu responds to forage availability regardless of the month of lactation. In spite of the low milk production levels in Zebu cattle, high within-breed variation in milk production has been observed with certain strains or individuals within the SEAZ type of cattle having very high milk production levels (Galukande et al, 1962). Farmers interviewed also observed this.…”
Section: Milk Productionmentioning
confidence: 99%